Promoting value chains of neglected and underutilized species for pro-poor growth and biodiversity conservation: Guidelines and good practices - Will, M.; Bioversity International; Global Facilitation Unit for Underutilized Species (2008)
This publication has been commissioned by the Global Facilitation Unit for Underutilized Species (GFU), created to ease and increase information and knowledge exchange in the field of neglected and underutilized species (NUS). GFU's mission is to promote and facilitate the sustainable deployment of underutilized plant species to increase food security and alleviate poverty among the rural and urban poor. Its objective is to support and strengthen organizations and networks working on different aspects of underutilized species through: providing improved access to information and financial resources; increasing public awareness on the role of underutilized species for improving livelihoods; and giving advice to policy-makers on how to create an enabling policy environment for the deployment of underutilized species. By doing so, GFU aims to attract an increasing number of assistance agencies, research institutions, extension services, policy- and decision-makers to include neglected and underutilized species in their development programmes.